Wetland environments : a global perspective - Aber, James S.; Pavri, Firooza; Aber, Susan Ward. (Chichester, West Sussex ; Hoboken, NJ : Wiley Blackwell, 2012)
Wetlands - swamp, marsh, bayou, tundra and bog - are places that are rarely visited and often misunderstood but they have, in fact, conspicuous roles in the physical, biological and cultural geography of the world. They are intrinsically beautiful environments where one may see the natural and essential values in the interaction of water, soil, vegetation, wildlife, and humans. Wetlands occur at the confluence of unique terrestrial, hydrological and climatic conditions that give rise to some of the most biodiverse regions of the world. They also play vital roles in the cycling and storage of key nutrients, materials and energy through the Earth?s system. A complete study of wetland environments requires the assessment of their physical and biological attributes, properties and functions of these ecosystems, and the economic, political and social aspects that mediate their use globally. A systems approach is taken throughout this book which emphasizes the interactions between these elements of wetland ecosystems. Moreover, selected case studies from across the world are used to illustrate wetland characteristics and circumstances. This book is intended to foster a greater awareness and appreciation of wetlands, promote a culture of conservation and wise management, and spread the knowledge that wetlands are important, indeed crucial, elements of the global environment. Our attempts to understand, manage and enhance wetlands in the twenty-first century are part of the larger effort to maintain a sustainable Earth.
9.4.1 Nordic region9.4.2 North America; 9.4.3 Tropics and Antarctica; 9.4.4 Holocene climate and early man; 9.5 Summary; 10: Environmental cycles and feedback; 10.1 Biogeochemical cycles; 10.1.1 Wetland elements; 10.1.2 Nitrogen; 10.1.3 Phosphorus, potassium and sulfur; 10.2 Carbon cycle; 10.2.1 Carbon reservoirs; 10.2.2 Carbon balance; 10.2.3 Carbon gases and climatic feedback; 10.3 Fossil fuels; 10.3.1 Fossil-fuel consumption; 10.3.2 Coal mining and acid rain; 10.3.3 Estonian oil shale; 10.4 Human experiment; 10.5 Summary; Part IV; 11: Wetland services, resources and valuation
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher.
Keywords: Wetlands; Wetland ecology; SCIENCE -- Earth Sciences -- Geography; SCIENCE -- Earth Sciences -- Geology; Wetland ecology; Wetlands; Electronic books; Electronic books; Electronic books